USER SATISFACTION ANALYSIS OF FACULTY OF ECONOMICS AND BUSINESS SERVICES, UNIVERSITAS JAMBI - Yudi, Yudi; Amin, Shofia; Indrawijaya, Sigit; Syeftiani, Try; Tialonawarmi, Feny (Journal of Business Studies and Management Review, 2025)
User satisfaction is one of the keys to success in managing an institution or organization. The level of service satisfaction is an important indicator to assess the extent to which service user expectations are met, by measuring the suitability between expectations of performance and the real experience felt after the service is used. The Community Satisfaction Index Survey conducted at the Faculty of Economics and Business uses a mixed method research approach. The population in this survey is all service users at the Faculty of Economics and Business, University of Jambi, including: lecturers, education staff, students, alumni, graduate users and cooperation partners. Furthermore, the sample in this survey is a portion of the representative population, using the Stratified Random Sampling technique. The results show that the Faculty of Economics and Business received a good assessment in terms of reliability, responsiveness, and certainty, but still needs to make improvements to infrastructure and accelerate the response of academic administration, especially for students. Keywords : Service Quality, User Satisfaction, FEB UNJA Services